Molecular surface coverage standards by reference-free GIXRF supporting SERS and SEIRA substrate benchmarking - Cara Eleonora; Hönicke Philipp; Kayser Yves; Beckhoff Burkhard; Giovannozzi Andrea M.; Klapetek Petr; Zoccante Alberto; Cossi Maurizio; Tay Li-Lin; Boarino Luca; Ferrarese Lupi Federico (Nanophotonics)
Non-destructive reference-free grazing incidence X-ray fluorescence (RF-GIXRF) is proposed as a highly effective analytical technique for extracting molecular arrangement density in self-assembled monolayers. The establishment of surface density standards through RF-GIXRF impacts various applications, from calibrating laboratory XRF setups to expanding its applicability in materials science, particularly in surface coating scenarios with molecular assemblies. Accurate determination of coverage density is crucial for proper functionalization and interaction, such as in assessing the surface concentration of probes on plasmonic nanostructures. However, limited synchrotron radiation access hinders widespread use, prompting the need for molecular surface density standards, especially for benchmarking substrates for surface-enhanced Raman and infrared absorption spectroscopies (SERS and SEIRA) as well as associated surface-enhanced techniques. Using reproducible densities on gold ensures a solid evaluation of the number of molecules contributing to enhanced signals, facilitating comparability across substrates. The research discusses the importance of employing molecular surface density standards for advancing the field of surface-enhanced spectroscopies, encouraging collaborative efforts in protocol development and benchmarking in surface science.